Analysis of medication adherence of chronic hypertensive patients in Pakistani community via open survey method - Sameen Abbas; Maida Noor; Ahmad Jalal Masood; Ejaz Ahmed; Arooba Shakeel; Muhammad Saad Ali; Usama Rizwan; Sohail Kamran (Open Exploration Publishing Inc., 2024)
Aim: Hypertension, a prevalent chronic condition, significantly contributes to cardiovascular diseases worldwide. Effective management of hypertension is highly dependent on patient adherence to prescribed medications, as the correct dose at the right time can lead to desirable therapeutic results. This study aims to analyze medication adherence among hypertensive patients in Islamabad and Rawalpindi through an open survey. Methods: A prospective cross-sectional study was conducted from 17th March 2024 to 30th May 2024, targeting hypertensive populations in Islamabad and Rawalpindi. 246 patients were recruited using a sample size formula, and a General Medication Adherence Scale (GMAS) questionnaire was used to collect data. All the tests were conducted as two-sided, with a significance level of P < 0.05 using Python. Results: Among 246 participants (mean age 57.1 years), most were married, literate, and living with families, 63% were from Islamabad, and 78.9% were employed. The study found high adherence in behavior-related areas but low adherence due to costs. Gender showed a statistically significant correlation (P = 0.03) by independent t-test. At the same time, ANOVA tests revealed that educational level (P = 0.02), monthly income (P = 0.001), family support (P = 0.04), and medication costs (P = 0.001) significantly impacted adherence, while factors like social status, employment status, and smoking did not have a considerable influence. Conclusions: 72.4% of patients adhered to their prescribed therapy, and 27.6% did not highlight a critical issue that requires urgent intervention. Variables like gender, educational status, social status, occupation, and living with family are strongly associated with adherence. Common problems include taking multiple medications, lack of awareness about the importance of adherence, and financial constraints.